DEVELOPMENT OF E-LEARNING APPLICATIONS AS A MEANS OF ONLINE LEARNING IN SMP AL AZHAR 1 BANDAR LAMPUNG - Satrianah Satrianah; Hilda Dwi Yunita (Jurnal TAM (Technology Acceptance Model), 2020)
In current teaching and learning activity on SMP Al Azhar 1 Lampung's Port, tutorial material application by teacher is done by use of conventional method.  In students appreciative data processing be done by use of calculator then menginput assesses student into excel's file then printed by that point data then that point data is kept in schooled cabinet so at alarms its happening lose point and damage data on students appreciative data. Base that thing therefore needed Application Development E Learning  As Medium Of Learning Online  at SMP Al Azhar 1 Lampung's Port. Base observational result in analyse Application Development E Learning  As Medium Of Learning Online  at SMP Al Azhar 1 Lampung's Port by use of system scheme utilize that web waters down deep implementation process and Application Development E Learning  As Medium Of Learning Online  at SMP Al Azhar 1 Lampung's Port.